2021
DOI: 10.1096/fj.202100426r
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia enhances procoagulant activity of vascular endothelial cells through TMEM16F regulated phosphatidylserine exposure and microparticle release

Abstract: The link between serum uric acid (SUA) and the risk of venous thromboembolism (VTE) is well established. Recent data suggested a causative role of UA in endothelial cells (ECs) dysfunction. However, the molecular mechanism of high UA on thrombogenesis is unknown. We investigate whether high UA induce phosphatidylserine (PS) externalization and microparticle (MP) shedding in cultured EC, and contribute to UA‐induced hypercoagulable state. In the present study, we demonstrate that UA induces PS exposure and EMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Moreover, the size is critical in determining the hemocompatibility of microparticles when administered parenterally. The human body naturally produces microparticles under pathologic conditions (e.g., cancer, endothelial alterations, inflammation) [59][60][61], resulting from membrane blebbing as part of cell apoptosis [62]. Artificial microparticles (e.g., DPNs) can mitigate this risk by minimizing protein adsorption (e.g., through their materials) and by tuning the particle materials properties (i.e., particle deformability and size).…”
Section: Particles In Systemic Administrationmentioning
confidence: 99%
“…Moreover, the size is critical in determining the hemocompatibility of microparticles when administered parenterally. The human body naturally produces microparticles under pathologic conditions (e.g., cancer, endothelial alterations, inflammation) [59][60][61], resulting from membrane blebbing as part of cell apoptosis [62]. Artificial microparticles (e.g., DPNs) can mitigate this risk by minimizing protein adsorption (e.g., through their materials) and by tuning the particle materials properties (i.e., particle deformability and size).…”
Section: Particles In Systemic Administrationmentioning
confidence: 99%
“…In addition, endothelial microparticles (MPs) participate in the mechanism underlying HUA‐induced coagulation. Yu et al 67 demonstrated that UA at high levels can induce cytoskeletal structure disruption, transmembrane protein 16F (TMEM16F) activation, phosphatidylserine (PS) externalization, and MP shedding in HUVECs by increasing the levels of intracellular calcium and ROS. After MP shedding and PS externalization on ECs, binding sites are made available for the coagulation factors FXA and the prothrombinase complex, which activate the coagulation cascade, resulting in a marked increase in thrombin generation and enhanced endothelial procoagulant activity (PCA) 67 .…”
Section: Mechanisms Underlying Hua‐induced Edmentioning
confidence: 99%
“…Yu et al 67 demonstrated that UA at high levels can induce cytoskeletal structure disruption, transmembrane protein 16F (TMEM16F) activation, phosphatidylserine (PS) externalization, and MP shedding in HUVECs by increasing the levels of intracellular calcium and ROS. After MP shedding and PS externalization on ECs, binding sites are made available for the coagulation factors FXA and the prothrombinase complex, which activate the coagulation cascade, resulting in a marked increase in thrombin generation and enhanced endothelial procoagulant activity (PCA) 67 . Collectively, these studies indicate that the interaction between ECs and coagulation‐fibrinolytic systems is altered in HUA, increasing the risk of thromboembolic events.…”
Section: Mechanisms Underlying Hua‐induced Edmentioning
confidence: 99%
“…1mL of blood was drawn into 3.8% sodium citrate tube from rats by cardiac puncture and mixed with 40μL kaolin. TEG analysis was performed according to Harmanpreet et al 25 , in brief, 340μL blood samples were placed into the prepared TEG cups with 20μL CaCl 2 (0.2M), and TEG analysis using a Haemoscope TEG 5000 Thrombelastograph Hemostasis Analyzer (Haemonetics Corp., Braintree, Massachusetts, USA) started immediately according to the manufacturer's instructions. The TEG run was stopped after all relevant parameters were assessed.…”
Section: Authorshipmentioning
confidence: 99%